Synthesis and Antimicrobial Study of 3,5,6-Trichloropyridine-2-yl(arylthio)acetate Derivatives - Shet, L.S.; Shelar, A.R. (Asian Journal of Chemistry, 2010)
Present invention related to synthesis of novel ester derivatives of 3,5,6-trichloropyridine-2-ol with aryl/naphthyl thioglycolic acid and substituted derivatives thereof as pharmaceutically active ingredients. This invention consists of synthesis of new pharmaceutical entities by reacting 3,5,6-trichloropyridine-2-ol with aryl/naphthyl thioglycolic acid halide and substituted derivatives thereof to get ester derivatives and to their use as antibacterial/antifungal agent. All these compounds were characterized by means of their melting point, HPLC, IR and 1H NMR spectroscopic data. The synthesized compounds (1a to 1d) have been screened for in vitro antibacterial activity against a variety of bacterial strains. Gram-negative strain of bacteria used were Klebsiella and E. coli while gram-positive bacterial strain used was Step. Aureus and E. fecalis The activity was determined using MIC. Ciprofloxacin was used as standard (2 μg/mL). The compounds have shown varying degree of antibacterial and antifungal activity.